Mathematical Thinking as Discourse: A Commognitive Analysis of Students with Different Problem-Solving Behavior - Ahmad Dzulfikar; Turmudi Turmudi; Tatang Herman; Kusnandi; Angga Hidayat (Mathematics Education Journal, 2026)
Mathematical thinking is essential in problem-solving, yet few studies have systematically examined differences in students’ mathematical thinking across analytical frameworks, particularly in relation to problem-solving behavior. This study investigates how different problem-solving behavior types reflect variations in students’ mathematical thinking processes from a commognitive perspective. An interpretive qualitative design with commognitive discourse analysis was employed. The participants were 35 students, from whom representatives of three problem-solving behavior groups were purposively selected for in-depth interviews. Data were collected through written tasks and semi-structured interviews and analyzed by examining word use, visual mediators, routines, and narratives. The findings revealed that students’ problem-solving behavior is associated with differences in their mathematical thinking processes. Students with sophisticated problem-solving behavior demonstrated explorative routines that produced substantiation narratives. Routine students showed specializing and generalizing processes but relied mainly on ritual routines and memorization narratives. In contrast, naïve students performed only limited specialization for number manipulation and failed to progress to other mathematical thinking stages, resulting in incorrect solutions. These findings clarify the relationship between mathematical thinking processes and problem-solving behavior and highlight the importance of fostering productive problem-solving behavior to strengthen students’ mathematical thinking in school mathematics.